Service Quality, Accessibility, and Brand Image Predict Passenger Satisfaction and Bus Usage in Surabaya: Kualitas Layanan, Aksesibilitas, dan Citra Merek Mempengaruhi Kepuasan Penumpang dan Penggunaan Bus di Surabaya - Sunubrata, Bramantio; Safirin, Moch.Tutuk (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Public transportation plays a vital role in supporting daily urban mobility, particularly in densely populated cities such as Surabaya, where efficient and reliable transit systems are increasingly needed. Suroboyo Bus serves as an urban public transport innovation that also promotes environmental sustainability through plastic bottle payment integration. Specific Background: Despite its innovative concept, Suroboyo Bus still faces operational challenges, including poor service quality, inadequate bus stop facilities, accessibility limitations, long waiting times, and application disruptions, which reduce passenger comfort and satisfaction. Knowledge Gap: Previous concerns indicate a mismatch between public expectations and actual service experience, yet limited studies have simultaneously examined service quality, accessibility, and brand image in relation to passenger satisfaction and reuse intention using Structural Equation Modeling. Aims: This study aims to analyze the relationships between service quality, accessibility, and brand image on passenger satisfaction and reuse intention among Suroboyo Bus users. Results: Using a quantitative survey of 110 respondents and SEM-AMOS analysis, the findings show that service quality, accessibility, and brand image each have positive and significant relationships with passenger satisfaction and reuse intention. Passenger satisfaction also shows a significant positive relationship with reuse intention, with the simultaneous model expressed as Y2 = 2.004 X1 + 1.874 X2 + 1.780 X3. Novelty: This study integrates these three determinants and confirms passenger satisfaction as a central mediating factor in public transport reuse behavior. Implications: The findings support managerial strategies focused on improving operational quality, expanding accessibility, and strengthening brand image to increase passenger satisfaction and encourage repeated use of Suroboyo Bus services. Highlights: Accessibility showed the strongest coefficient in shaping passenger satisfaction among the examined variables. Passenger satisfaction demonstrated a strong direct relationship with repeated use decisions. Integrated SEM results confirmed all proposed relationships were statistically significant. Keywords: Passenger Satisfaction, Reuse Intention, SEM, Suroboyo Bus